Staining for soybean lipoxygenase activity in electrophoretic gels - Heinisch, Oliver; Kowalski, Elisabeth; Ludwig, Horst; Tauscher, Bernhard (Fett, 1996)
A staining method for lipoxygenase in electrophoretic gels is described which is based on the staining of hydroperoxides, as reaction products of added substrates, by N,N-dimethyl-p-phenylenediamine. Soybean lipoxygenase (EC 1.13.11.12) was detected after gel electrophoresis for anodic proteins under non-denaturating conditions and was compared to soybean lipoxygenase stained by Coomassie Brilliant Blue. Specifity of the method was checked by use of heat-denaturated lipoxygenase, tyrosinase and substrate absence. Staining intensity has been found to be proportional to the enzyme activity.
Gesehen am 12.02.2026